SUSTAINABILITY Of AGRICULTURE: THE NEOLITHIC DILEMMA - Flynn, Dave (Archives of Business Research, 2019)
Water resources are being threatened by the use of fertilizers in farming in developing and developed countries. Significant changes are required of the world farming community to use more sustainable agricultural practices, otherwise the availability of clean water resources will reach catastrophically low levels worldwide. Suggestions are provided for reaching sustainable outcomes as the agriculture industry is necessary for feeding an ever growing world population.